Why the professional-Client Ethic is Inadequate in Mental Health Care - Leung, Wai-Ching (Nursing ethics, 2002)
Patients who are subject to compulsory care constitute a substantial proportion of the work-load of mental health professionals, particularly psychiatric nurses. This article examines the traditional ‘beneficence-autonomy’ approach to ethics in compulsory psychiatric care and evaluates it against the reality of daily practice. Risk to the public has always been an important but often unacknowledged consideration. Inequalities exist among ethnic and socio-economic groups and there is a lack of agreement on what constitutes mental disorder. Two major changes in compulsory psychiatric care - community orders and care for patients with untreatable severe personality disorders - further challenge the traditional ethical approach. There are also important human rights implications. The simple patient-health professional relationship no longer provides an adequate framework for mental health professionals on which to base their ethical decisions. The public and organizations may have different perspectives and their interests are becoming increasingly important. Mental health professionals, particularly psychiatric nurses, may face ethical dilemmas because of these different perspectives.